Cytoreductive Surgical Treatment of Pleural Mesothelioma in a Porcine Model Using Magnetic-Resonance-Guided Focused Ultrasound Surgery (MRgFUS) and Radiofrequency Ablation (RFA) - Marcia Costa; Carolina Fernandes; Matt Eames; Arik Hananel; John P. Mugler; Jhosep Huaromo; Jack B. Yang; Jaime Mata (Tomography, 2022)
A combination of surgery and chemotherapy is the most effective treatment available for Malignant Pleural Mesothelioma (MPM). However, both cause significant collateral damage and cannot eliminate residual microscopic disease. This investigation aimed to compare and determine the feasibility of utilizing Radiofrequency Ablation (RFA) and Magnetic-Resonance-guided Focused Ultrasound Surgery (MRgFUS) as alternative treatments for MPM. A large animal tumor model was developed in 13 Yorkshire female pigs using the MSTO211H cell line. Two pigs were initially used to determine the cyclosporine dose required for immunosuppression and tumor development. Subsequently, 11 other pigs underwent tumor development. Of these 11, 2 died during cell inoculation. Small tumor masses and adhesions were present in the other 9, indicating mesothelioma development. Five pigs then received RFA treatment, and 4 pigs received MRgFUS treatment. Tumor model development and effect of the two treatments were examined using MRI and by necropsy. RFA and MRgFUS both successfully ablated approximately the same sized area in the same treatment time. This study demonstrates that RFA and MRgFUS are feasible for tumor debulking, and while MRgFUS requires more pretreatment planning compared to RFA, MRgFUS is a completely noninvasive procedure.